2014
DOI: 10.1186/1477-7525-12-59
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of health-related quality of life among the empty-nest elderly in rural China: An empirical study in three economically developed cities in eastern China

Abstract: BackgroundAlong with rapid economic development, the aging process in China is gradually accelerating. The living conditions of empty-nest rural elderly are worrisome. As a more vulnerable group, empty-nest elderly are facing more urgent health problems. This study explores the health-related quality of life (HRQOL) of empty-nest elderly in rural China and aims to arouse more social concern for their HRQOL.MethodsResearch subjects were empty-nest rural elderly from three cities: Nanjing, Suzhou, and Wenzhou (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 64 publications
5
84
0
2
Order By: Relevance
“…Previous studies have also revealed that HALE differs by gender and ethnicity. In general, women have a longer LE than that of men (11, 12) but are more likely to suffer problems such as depression (13), loneliness, and empty-nest syndrome in late life (14). Contrarily, men tend to report better quality of life (15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also revealed that HALE differs by gender and ethnicity. In general, women have a longer LE than that of men (11, 12) but are more likely to suffer problems such as depression (13), loneliness, and empty-nest syndrome in late life (14). Contrarily, men tend to report better quality of life (15).…”
Section: Introductionmentioning
confidence: 99%
“…Quando os filhos se retiram da casa dos seus pais caracteriza-se o fenômeno do ninho vazio, pois o lar passa a abrigar apenas a família conjugal, cenário que pode representar um risco de sobrecarga e esgotamento do cuidador 17 .…”
Section: Discussionunclassified
“…This occurrence is closely related to economic prosperity and one-child policy. With the accelerated process of urbanization and the flow of rural surplus labor to big cities, some farmers have established their careers in big cities and become urban dwellers, while their parents are left behind in rural homes [31,32]. And the one-child policy makes many families' structured as 4-2-1 as the first generation of only children has reached their marrying age.…”
Section: Barriers To Realize Assisted Pdmentioning
confidence: 99%
“…And the one-child policy makes many families' structured as 4-2-1 as the first generation of only children has reached their marrying age. A young married couple has to take care of two sets of parents without help from siblings [31]. For such PD empty-nest elderly, implement assPD by trained home-care nurses seem is an attractive option.…”
Section: Barriers To Realize Assisted Pdmentioning
confidence: 99%